Catalytic Performance of Fe-Mn/SiO2 Nanocatalysts for CO Hydrogenation - Mostafa Feyzi; Shirin Nadri; Mohammad Joshaghani (Journal of Chemistry)
A series of x(Fe, Mn)/SiO2 nanocatalysts (x=5, 10, 15, 20, 25, and 30 wt.%) were prepared by sol-gel method and studied for the light olefins production from synthesis gas. It was found that the catalyst containing 20 wt.% (Fe, Mn)/SiO2 is an optimal nano catalyst for production of C2–C4 olefins. Effects of sulfur treatment on the catalyst performance of optimal catalyst have been studied by espousing different volume fractions of H2S in a fixed bed stainless steel reactor. The results show that the catalyst treated with 6 v% of H2S had high catalytic performance for C2–C4 light olefins production. The best operational conditions were H2/CO = 3/2 molar feed ratio at 260°C and GHSV = 1100 h−1 under 1 bar total pressure. Characterization of catalysts was carried out using X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and surface area measurements.